2009
DOI: 10.1088/0022-3727/42/13/135203
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering yields of Au by low-energy noble gas ion bombardment

Abstract: Sputtering yields of gold (Au) by noble gas (He, Ne, Ar, Kr or Xe) ions have been measured in the low injection energy range 25–200 eV. The yield data presented here were obtained from mass-selected ion beam sputtering experiments, in which the ion beam has a very narrow energy spread and contains no impurity ions. The newly obtained yield data set, together with the fitting functions for the yield dependence on the injection energy, provide an accurate and reliable database for the study of fundamental physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The mass resolution of the QCM system is 2:4 Â 10 À11 g. The QCM surface temperature is initially set at room temperature but not actively controlled during the experiment. With this QCM system, we have measured sputtering yields of Au by He þ , Ne þ , Ar þ , Kr þ , or Xe þ ion beams 16) and have found that the measured sputtering yields agreed with earlier data obtained by other groups. [18][19][20][21][22][23][24][25][26] A mass and energy detector (Balzers PPM421) is placed immediately behind the Faraday cup and the QCM.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The mass resolution of the QCM system is 2:4 Â 10 À11 g. The QCM surface temperature is initially set at room temperature but not actively controlled during the experiment. With this QCM system, we have measured sputtering yields of Au by He þ , Ne þ , Ar þ , Kr þ , or Xe þ ion beams 16) and have found that the measured sputtering yields agreed with earlier data obtained by other groups. [18][19][20][21][22][23][24][25][26] A mass and energy detector (Balzers PPM421) is placed immediately behind the Faraday cup and the QCM.…”
Section: Methodssupporting
confidence: 82%
“…Therefore, we focus on the energy range of 100-300 eV, which is accessible by the beam system used in this study. [8][9][10][11][12][13][14][15][16][17] Although the energy range we studied in this work is higher than typical ion energies in a PDP cell, the data we present here may offer some insight into characteristics of sputtering under the extremely low energy conditions relevant for PDP cells.…”
Section: Introductionmentioning
confidence: 89%
“…The film mass change on the QCM crystal can be monitored by a QCM controller (ULVAC-CRTM9000). The mass resolution of the QCM system is 2.4×10 −11 g. With this QCM system, we have measured sputtering yields of Au [8] and magnesium oxide (MgO) [9,10] by He, Ne, Ar, Kr, or Xe ion beams and found that the measured sputtering yields agree well with earlier data obtained by other experimental groups.…”
Section: Methodssupporting
confidence: 79%
“…[20]. With this system, we have measured sputtering yields of MgO [20] and Au [21] by He, Ne, Ar, Kr, and Xe ion beams. The measured sputtering yields of Au and MgO agree well with earlier data obtained by other experimental groups.…”
Section: B Gallium Ion Beam Experimentsmentioning
confidence: 99%